KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA SEMARANG - Zulhuda, Farikh; ., Turtiantoro; ., Sulistyowati (Journal of Politic and Government Studies, 2017)
The purpose of this study is to determine the contribution of Hotel Tax to Local Revenue and obstacles in the tax collection of hotels in Semarang City Government and the efforts made by the Office of Management of Finance and Regional Assets Semarang City to increase the acceptance of Hotel Tax.This research method used descriptive qualitative research method with library data collection and field study which consist of observation, documentation and interview. The research object used is Hotel Tax and Local Taxes obtained from the Office of Financial Management and Regional Assets Semarang City Government in 2011 to 2015. In this study researchers used secondary data and primary data. Primary data is data obtained in the form of words and actions from the results of interviews with informants. Informants from this research are employees of the Office of Financial Management and Regional Assets Semarang City. While secondary data is data obtained from literature books, documents, statistical data or archives from the Office of Financial Management and Regional Assets Semarang City.Based on the results of the research note that the development of hotel taxes in 2011 up to 2015 continues to increase with the average rate of hotel tax growth per year 15.6% although income from Hotel Tax always increase every year but its contribution to the Original Regional Revenue shows results in category is very less with an average of 4.98% from 2011-2015. The obstacles encountered are lack of human resources and still low awareness in paying taxes.Keywords : Contributions, Hotel Tax and Local Own Revenue